A Modified Synthetic Pathway for the Synthesis of so far Inaccessible N1‐Functionalized Tetrazole Ligands – Synthesis and Characterization of the 1D Chain‐Type Spin Crossover Compound [Fe(3ditz)3](BF4)2. Issue 5 (17th January 2013) - Müller, Danny; Knoll, Christian; Stöger, Berthold; Artner, Werner; Reissner, Michael; Weinberger, Peter
Abstract: A modified phase‐transfer‐catalyst‐assisted synthetic pathway was developed that widens the pool of accessible 1‐substituted tetrazoles, which are possible ligands for iron(II) spin‐crossover compounds. Within the family of α, ω‐bis(tetrazol‐1‐yl)alkanes, a series of ligands and their respective iron(II) spin‐crossover compounds were synthesized and structurally and spectroscopically characterized in the past. The classical route to prepare these ligands is based on the respective amino‐precursors. Hence the pool of accessible compounds is limited by the commercial or synthetical availability of α, ω‐diaminoalkanes. Furthermore, the concomitant transformation to the tetrazole moieties turns out to be easier for diamino‐alkanes with an even number of carbon atoms than for those with an odd number. In line with this observation, the shortest odd‐numbered homologues such as 1, 1‐bis(tetrazol‐1‐yl)methane ( 1ditz ) and 1, 3‐bis(tetrazol‐1‐yl)propane ( 3ditz ) were inaccessible so far. In this paper, we report the successful preparation and characterisation of the classically inaccessible 1, 3‐bis(tetrazol‐1‐yl)propane ( 3ditz ) and of its spin‐crossover complex [Fe( 3ditz )3 ](BF4 )2, which features an abrupt and almost complete spin transition at T ${1 \over 2}$ = 159 K. The single‐crystal X‐ray structure of the low‐spin and the high‐spin species is presented. The magnetic data are supported by variable‐temperature IR, UV/Vis/NIR, and 57 Fe Mössbauer spectra. Abstract : A "new" synthetic "pathway" allows the preparation of tetrazole ligands that were so far not accessible. The synthesis and characterization of new spin‐crossover compound [Fe( 3ditz )3 ](BF4 )2 is described. Despite of the flexibility of the 1, 3‐bis(tetrazol‐1‐yl)propane ( 3ditz ) ligand, a perfect packing of the coordination polymer enhances the cooperativity of the spin transition at T ${1 \over 2}$ = 159 K.